Decrease in the vaccination coverage related to age group, Rio de Janeiro Municipality, Brazil (Research, Society and Development, 2021)
Objective: to analyze vaccination coverage in the city of Rio de Janeiro, related to age groups, in the period 2013-2019. Methodology: descriptive, ecological, analytical, quantitative and cross-sectional study. Calculation of vaccine coverage through the ratio between the doses applied, available on the free access website of the Ministry of Health, Department of Informatics of the Unified Health System (DATASUS/TABNET) and target population, registered in the Information System on Live Births (SINASC) or population estimates found at the Brazilian Institute of Geography and Statistics Foundation (IBGE). Results: the indicators obtained for immunobiologicals that make up the vaccination calendar for newborns, children and adolescents reveal a worrying scenario of accentuation of the fall in vaccination coverage, according to each age group, with few successful indicators. Conclusion: the results of this study highlight the drop in vaccination coverage for some vaccines and age groups. It indicates the need for studies to investigate the reasons that have led to this drop in vaccination coverage.